An Analytical Study of the Problems of Translating Collocations: A Translation from French into English of an Extract from ‘Guide Juridique Et Fiscal Des Associationsau Togo “Tome II - Anamoah, E.E. (University of Ghana, 2019)
Translation has been with human interaction from the time of creation. Scholars have found it necessary to set up frameworks for the regulation of translation due to variation and the peculiarities of languages. The study examines and analyzes the problems that may be encountered in the process of translating collocations. The source text is a legal document. Chapter one looks at the history of translation and the process of organization of translation as a field of study. The implications of translation on globalization and integration of nations was also examined. Due to the increased trend of integration and need for communication among peoples of different languages, the issue of collocations and their nature were examined. Previous studies on collocations: definitions, characteristics and relevance to translation were also assessed. Chapter Two is the translation of the text “Guide juridique et fiscal des associations au Togo” Tome II. A brief introduction of the source text was done. A translation of the text which is a legal document - administrative and tax manual was done. Chapter Three analyzes and discusses the problems encountered in the translation of collocations, from the source text into the target language and solutions. Conclusions made from the study are also in this chapter. It was realized that collocations take a significant chunk of most texts. They are therefore relevant to the study of translation and to the mastery of language. Collocations were not found in the text were not necessarily monosemous. Collocations in technical text may be ambiguous and polysemous. Functional equivalence has implications in the translation of collocations in technical text. It was also realized that one needs to know the collocational ranges of lexical items, to enable make appropriate choices for a faithful translation. Keywords: Analytical Study, Collocations, Concordance, Collocational Range, Legal Text
MA. Translation
Keywords: Analytical Study; Collocations; Concordance; Collocational Range; Legal Text